2019
DOI: 10.1021/bk-2019-1333.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Black Phosphorus upon Environmental Exposure and Encapsulation Strategies To Prevent It

Abstract: Along this chapter we discuss about one of the main issues in black phosphorus research: its environmental instability. We will discuss the works were the role of the environmental exposure has been studied and the reported works describing strategies to effectively encapsulate black phosphorus to preserve its pristine properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…[ 7 ] This has been a drawback to its device compliance in lots of applications. Strategies like encapsulation, [ 8 ] surface passivation, [ 9 ] surface functionalization, [ 10 ] and doping [ 7 , 11 ] have been developed with varying degrees of success to help enhance the stability of phosphorene. Phosphorene starts degrading from the surface [ 12 ] as oxygen molecules approach with an exothermic energy of −4.07 eV per molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] This has been a drawback to its device compliance in lots of applications. Strategies like encapsulation, [ 8 ] surface passivation, [ 9 ] surface functionalization, [ 10 ] and doping [ 7 , 11 ] have been developed with varying degrees of success to help enhance the stability of phosphorene. Phosphorene starts degrading from the surface [ 12 ] as oxygen molecules approach with an exothermic energy of −4.07 eV per molecule.…”
Section: Introductionmentioning
confidence: 99%
“…5 e), the result reflected that BP with thickness less than 10 nm showed faster degradation under ambient conditions, which indicated that the degradation of BP was also thickness-dependent. The structural failure caused by the degradation will affect the intrinsic properties of phosphorene and bring difficulties to its practical application in device [ 98 , 99 ]. However, on the other hand, Wu et al [ 100 ] suggested that the degradation of BP actually has a positive side.…”
Section: Environmental Instability and Passivationmentioning
confidence: 99%